2005
DOI: 10.1097/01.ju.0000148326.71981.44
|View full text |Cite
|
Sign up to set email alerts
|

DETECTION OF PROSTATE CANCER WITH 11 C-METHIONINE POSITRON EMISSION TOMOGRAPHY

Abstract: MET PET of the prostate with short dynamic scanning and multicore biopsy is a useful method to ensure a high detection rate of prostate cancer in patients with increased PSA and repeat negative biopsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 12 publications
1
29
0
3
Order By: Relevance
“…11 Cmethionine is an amino acid radiotracer that, in limited studies, demonstrated a sensitivity of 72% in the detection of metastatic prostate cancer ( 44 ) and an overall detection rate of 46.7% for primary carcinoma ( 51 ).…”
mentioning
confidence: 99%
“…11 Cmethionine is an amino acid radiotracer that, in limited studies, demonstrated a sensitivity of 72% in the detection of metastatic prostate cancer ( 44 ) and an overall detection rate of 46.7% for primary carcinoma ( 51 ).…”
mentioning
confidence: 99%
“…Suspect 11 C-MET uptake was noted in 75% of subjects (15/20), 46.7% of whom (7/15) had prostate cancer confirmed by 11 C-MET-guided biopsy (28). However, the fact that 8 subjects with focal 11 C-MET uptake and negative guided biopsies had either benign prostatic hyperplasia (6/8) or chronic prostatitis (2/8) demonstrates a limitation in the evaluation of primary prostate cancer.…”
Section: Investigations With Radiolabeled Naturally Occurring Amino Amentioning
confidence: 90%
“…Radiolabeled naturally occurring amino acids, such as L-11 Cmethionine ( 11 C-MET) and L-1-11 C-5-hydroxytryptophan, were the first radiotracers used in amino acid-based molecular imaging of prostate cancer (26)(27)(28)(29).…”
Section: Investigations With Radiolabeled Naturally Occurring Amino Amentioning
confidence: 99%
“…11 C-choline and 18 F-fluorocholine are widely used PET radiotracers for prostate cancer imaging (9,20), but also 11 C-methionine and 11 C-acetate PET have been successfully tested for this indication (32,33). 11 C-choline is known to be rapidly transported into human cancers, including prostate cancer.…”
Section: Discussionmentioning
confidence: 99%